Zebrafish as an alternative animal model in human and animal vaccination research - Bailone, Ricardo Lacava [UNESP]; Fukushima, Hirla Costa Silva; Ventura Fernandes, Bianca Helena; De Aguiar, Luis Kluwe; Correa, Tatiana; Janke, Helena; Grejo Setti, Princia; Roca, Roberto De Oliveira [UNESP]; Borra, Ricardo Carneiro (Springer, 2020)
Much of medical research relies on animal models to deepen knowledge of the causes of animal and human diseases, as well as to enable the development of innovative therapies. Despite rodents being the most widely used research model worldwide, in recent decades, the use of the zebrafish (Danio rerio) model has exponentially been adopted among the scientific community. This is because such a small tropical freshwater teleost fish has crucial genetic, anatomical and physiological homology with mammals. Therefore, zebrafish constitutes an excellent experimental model for behavioral, genetic and toxicological studies which unravels the mechanism of various human diseases. Furthermore, it serves well to test new therapeutic agents, such as the safety of new vaccines. The aim of this review was to provide a systematic literature review on the most recent studies carried out on the topic. It presents numerous advantages of this type of animal model in tests of efficacy and safety of both animal and human vaccines, thus highlighting gains in time and cost reduction of research and analyzes.
Keywords: 3Rs; Animal health; Human health; Immunity; Toxicology; Vaccine safety